Communicative Language Teaching: Changing Students’ Speaking Skill - Juni Bayu Saputra (Premise: Journal of English Education and Applied Linguistics, 2015)
ABSTRACTThis article points out the results of the study attempting to solve the speaking problem faced by students in one of the Higher School of Teacher Training and Education (STKIP) in Central Lampung. For the purpose of the topic, 30 fellow students were selected as the subject. Research method was Classroom Action Research with Kemmis and Taggart model. It was conducted for about four cycles. According to the results of speaking test, findings showed that using Communicative Language Teaching (CLT) had positive meaningful effect on improving students’ speaking skill. To sum up, CLT is an effective method to teach speaking to the subject.